More Relaxation by Deep Breath on Methacholine- Than on Exercise-Induced bronchoconstriction during the Routine Testing of Asthmatic Children - Ioan, Iulia; Tatopoulos, Aurélie; Metche, Stéphanie; Coutier, Laurianne; Houriez, Emmanuelle; Kiefer, Sébastien; Blondé, Aurore; Bonabel, Claude; Marchal, François; Derelle, Jocelyne; Schweitzer, Cyril E.; Demoulin-Alexikova, Silvia (Frontiers in Physiology, 2017)
Deep inhalation (DI) dilates normal airway precontracted with methacholine. The fact that this effect is diminished or absent in asthma could be explained by the presence of bronchial inflammation. The hypothesis was tested that DI induces more relaxation in methacholine induced bronchoconstriction – solely determined by the smooth muscle contraction – than in exercise induced bronchoconstriction, which is contributed to by both smooth muscle contraction and airway wall inflammation. The respiratory conductance (Grs) response to DI was monitored in asthmatic children presenting a moderately positive airway response to challenge by methacholine (n = 36) or exercise (n = 37), and expressed as the post- to pre-DI Grs ratio (GrsDI). Both groups showed similar change in FEV1 after challenge and performed a DI of similar amplitude. GrsDI however was significantly larger in methacholine than in exercise induced bronchoconstriction (p < 0.02). The bronchodilatory effect of DI is thus less during exercise- than methacholine-induced bronchoconstriction. The observation is consistent with airway wall inflammation – that characterizes exercise induced bronchoconstriction – rendering the airways less responsive to DI. More generally, it is surmised that less relief of bronchoconstriction by DI is to be expected during indirect than direct airway challenge. The current suggestion that airway smooth muscle constriction and airway wall inflammation may result in opposing effects on the bronchomotor action of DI opens important perspective to the routine testing of asthmatic children. New crossover research protocols comparing the mechanical consequences of the DI maneuver are warranted during direct and indirect bronchial challenges.